Glycyrrhizic acid Poly(D,L-lactide-coglycolide) nanoparticles: anti-aging cosmeceutical formulation for topical applications - Aluc, Cigdem Cetin; Gok, Bahar; Kecel-Gunduz, Serda; Budama-Kilinc, Yasemin (PEERJ INC, 2022)
Glycyrrhizic acid (GA) is one of the components of licorice roots (Glycyrrhiza glabra L.). GA is a triterpenoid saponin can be used as a medicinal plant with its antiallergic, antiviral, anti-inflammatory, anti-ulcer, hepatoprotective, anticancer, anti-oxidation activities and several other therapeutic properties. The aim of this study is to develop an anti-aging formulation for topical application containing GA. In this context, GA-loaded Poly (D,L-lactide-co-glycolide) (PLGA) nanoparticles (NPs) were prepared using the double emulsion method, and were characterized by various spectroscopic methods. The efficacy of GA-PLGA NPs was evaluated with in vitro and in silico methods. The encapsulation efficiency and loading capacity were calculated. The in vitro release study was conducted, and the GA release profile was determined. The genotoxic activity of GA and GA-PLGA NPs was evaluated by the Ames test using TA98 and TA100 mutant strains of Salmonella typhimurium. The cytotoxic potential of GA-PLGA NPs was evaluated on the HaCaT cell line using the MTT assay. According to the genotoxicity and cytotoxicity results, it was found that the GA-PLGA NP formulation did not exhibit genotoxic and cytotoxic effects. Moreover, the efficacy of GA in preventing UVB-induced photo-aging in HaCaT cells and the clarification of the molecular mechanism of GA binding to MMPs were revealed by molecular docking analysis. In addition, through molecular dynamics (MD) analysis, the binding interaction of GA with MMPs in a dynamic system, and protein-ligand stability were predicted as a result of 50 ns MD simulation studies considering various analysis parameters. Finally, it was evaluated that GA-PLGA nanoformulation might be used as an alternative anti-aging skin care product candidate via topical application.
Keywords: Glycyrrhizic acid; Nanoparticles; PLGA; Genotoxicity; Cytotoxicity Molecular docking; MD; LOADED PLGA NANOPARTICLES; MOLECULAR DOCKING; ACCURATE DOCKING; PLANT-EXTRACTS; IN-VITRO; SKIN; ANTIOXIDANT; GLIDE; INHIBITOR; Science & Technology - Other Topics